(untitled) (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: In 2013 Midwifery Academy Yogyakarta formed a partnership with Ministry of Disadvantaged Areas with the aim that graduates could be health workers in disadvantaged areas. West Nusa Tenggara still lacking midwives has set midwives as PTT (civil impermanent servants). This study investigates the Antenatal Care competence of midwives in maternity care. Objective: to know how competence of midwifery academy graduates in providing antenatal care in West Nusa Tenggara province. Methods: The research method mixed quantitative and qualitative survey using questionnaires and interviews. The population comprised all alumni of Yogyakarta Midwifery Academy from the province of West Nusa Tenggara in Mei- July 2014. The samples were taken by purposive sampling representing alumni working in primary health centers, hospitals, and independent practice Results: The alumni were 62 midwives. Most were working in Polindes or primary health center, having no integrated services mainly for laboratory examination. Midwives working in hospitals do not necessarily provide antenatal care, depending on their ward assignation. Complications or referral services were conducted in accordance with standard procedures. Length of working experience improves the ability of midwives in the early detection of complications and referral. Conclusions and suggestions: Antenatal care competence was in accordance with procedures. Midwives should increase their knowledge and skills in accordance with the government program. Keywords: midwife competence, antenatal care.